2011
DOI: 10.1614/ws-d-10-00153.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage and Burial on Germination Responses of Encapsulated and Naked Seeds of Turnipweed (Rapistrum rugosum) to Light

Abstract: Information on the germination and viability of turnipweed seeds could be helpful in developing appropriate management strategies for this weed. Therefore, experiments were conducted to investigate the effects of light, storage conditions, duration of storage or burial, and seed type (naked, i.e., fruit wall was removed and encapsulated in siliques) on germination and viability of turnipweed. The naked and encapsulated seeds (fruit) were kept under five different storage conditions, including dry storage at 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…A similar result was found in the Brassicaceae species R. raphanistrum (Cousens et al 2010), D. strictus (Lu et al 2010) and I. violascens (Zhou et al 2015). One way in which the pericarp can inhibit germination is via mechanical resistance (Cousens et al 2010;Lu et al 2010;Ohadi et al 2011;Mamut et al 2014). That is, the embryo does not have enough growth potential to overcome the mechanical resistance of the pericarp and other covering layers (endosperm, seed coat) until the seeds become non-dormant.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A similar result was found in the Brassicaceae species R. raphanistrum (Cousens et al 2010), D. strictus (Lu et al 2010) and I. violascens (Zhou et al 2015). One way in which the pericarp can inhibit germination is via mechanical resistance (Cousens et al 2010;Lu et al 2010;Ohadi et al 2011;Mamut et al 2014). That is, the embryo does not have enough growth potential to overcome the mechanical resistance of the pericarp and other covering layers (endosperm, seed coat) until the seeds become non-dormant.…”
Section: Discussionsupporting
confidence: 68%
“…They may (i) protect seeds against predation by animals (Cousens et al 2010); (ii) prevent germination during unfavourable environmental conditions for seedling survival (Cousens et al 2010;Lu et al 2010;Ohadi et al 2011); (iii) provide an internal environment that keeps the seed moist after a period of moderate rainfall (Mamut et al 2014;Zhou et al 2015), thus extending the effective period over which germination can occur, or enabling a germinating seedling to survive until the next rainfall event through slowing desiccation (Cousens et al 2010;Mamut et al 2014); and/or (iv) inhibit germination and spread the timing of germination of seeds in a given cohort over several years (Lu et al 2015b), which may be a bet-hedging strategy. In L. filifolium and N. korolkovii, opening of the pericarp only after the fruits have been wet for a few days helps ensure that there is adequate soil moisture for seedling establishment at the time seeds germinate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3; Lu et al, unpublished data). In Rapistrum rugosum, Ohadi et al (2011) reported that dormancy was caused by the pericarp, but Cousens et al (1994) concluded that dormancy in distal seeds (in the fruit of this species) may also, at least in part, be due to the seed coat and/ or embryo. 2), suggesting that the embryo lacked enough growth potential (push power) to overcome the mechanical Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…The Brassicaceae includes many species with dry dehiscent as well as those with dry indehiscent fruits, and previous research on the effect of the pericarp on germination reveals that it may prevent germination in this family (Mekenian and Willemsen, 1975;Cheam, 1986;Cousens et al, 2010;Lu et al, 2010;Ohadi et al, 2011;Mamut et al, 2014). To understand the germination ecology of species with such fruits, the role of the pericarp in delaying and/or promoting germination must be considered.…”
Section: Introductionmentioning
confidence: 99%